Dampak Multivariat Volatility, Contagion dan Spillover Effect Pasar Keuangan Global terhadap lndeks Saham dan Nilai Tukar Rupiah di Indonesia - Trihadmini, Nuning; B. S. W., Pudjiastuti (Jurnal Ekonomi dan Pembangunan Indonesia, 2011)
There are several factors influencing the financial system stability, namely the internal and the external factors. The occurrence of stock price volatility internationally, the contagion effects and the spillover effects are some external factors that have effect on the financial system stability. This research aims to know the dynamic relationship of regional and global stocks market in international financial system, and then do the analysis of the occurrence of contagion effects and spillover effects on stock price, and see their influence on domestic economics, monetary policy and financial system stability, by GARCH-VAR model.The results of this research indicate that there are some domination of the mature financial market to regional and domestic market. Moreover, the nearby regional stock price index also have a big contribution to the movement of other regional stock price market. The impact of stock price volatility to the IDR exchange rates volatility is relatively small, but not to the price level which is significantly large. Data analysis shows that there is contagion effects in stock market, but the spillover effect from stock price volatility to exchange rates volatility does not occur.